On the status shocks of tournament rituals: How ritual enactment affects productivity, input provision, and performance - MAORET, Massimo (Institutional Knowledge at Singapore Management University, 2023)
We propose a novel process through which status shocks may enhance performance. Specifically, we theorize that when status shocks include a ritualistic conferment of social prestige – such as in the case of “tournament rituals” – participating in that ritual enactment may increase tournament winners’ productivity and improve the inputs they receive, thereby improving their overall performance. We also consider the duration of that performance improvement, finding a decay that is consistent with our theorized mechanisms that are based on emotional energy. Our study shows that status shocks carry not only informational value, as signals of quality, but also symbolic and social value that change the behavior of individuals who receive these shocks and of the input providers with whom they interact. We employ difference-in-differences and regression discontinuity designs on game-level data from the National Basketball Association (NBA) to provide causal evidence for our hypotheses.